Silent Treatment as an Interpretation of Ila' in the Problems of the Digital Era Perspective of Tafsir al-Misbah - Muhammad Waliyuddin Yusuf; Muflikhatul Khoiroh; Suqiyah Musaf’ah; Nichatus Sholikah (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2025)
The phenomenon of silent treatment in the digital era—manifested through ghosting, seen-zoning, and blocking—reflects a communication crisis that affects psychological well-being and the stability of family relationships. This practice bears an essential resemblance to the classical Islamic concept of Il?’. This study aims to analyze the connection between Il?’ and silent treatment through the perspective of M. Quraish Shihab’s Tafsir al-Mishbah. The research employs a normative-prescriptive legal method with a qualitative, literature-based approach, examining Qur’anic verses on Il?’, classical fiqh literature, modern psychological studies, and contemporary family law regulations. The findings show that the Qur’an limits Il?’ to four months to prevent emotional neglect, whereas digital silent treatment is unrestricted and tends to become a form of psychological abuse. Tafsir al-Mishbah emphasizes ethical communication and mu‘?syarah bi al-ma‘r?f as corrective principles for modern relational neglect. The study concludes that the corrective values of Il?’ are relevant for formulating communication guidelines in digital-era family life.